Diseño y construcción de un tablero didáctico para realizar prácticas de mediciones en corriente alterna. - Correa Rojas, Carlos Alberto (2014)
The study of the mensurations of alternating current is a topic of supreme importance for the applied sciences, for which will be contributed to the improvement of the process teaching learning of the students of the Área with the construction of the didactic board, this board gives the possibility to carry out connections or circuits where the current magnitudes and voltage can be measured when alternating current is applied. To feed the circuits a transformer reducer it has been located whose power is of 900 VA, the current in the secondary one is of 25 A, and voltages havening of 3, 6, 9, 12, 24 and 36 V for the practical realization of the different ones that they are presently in detailed form report. In the board all the components are very organized and presented in such a way that are motivating for the students, we have been chosen different components as resisters, inductors and capacitors that allow carrying out the practices of circuits RLC without any difficulty. We have been developed the outlined practices correctly and the obtained results have given execution with the objectives outlined in the project. Through this didactic team it is projected to that the students may enlarge the knowledge by means of the development of experiences to the moment to make a practice, in the board different types of connections can be executed, to measure voltages and currents that can be compared with the calculated data. The measures of the didactic board are 85 cm X 130 cm X 52.5 cm, it is built in wood and have two sections, the first are placed all the measure instruments, protection and feeding, in the other section all the components for consistent experimentation in resisters, inductors and capacitors. For a correct use of the board we have been carried out a guide of practical.